Unlocking the depths: multiple factors contribute to risk for hypoxic blackout during deep freediving - Mulder, E.; Staunton, C.; Sieber, A.; Schagatay, E. (European Journal of Applied Physiology, 2023)
Purpose To examine the effect of freediving depth on risk for hypoxic blackout by recording arterial oxygen saturation (SpO2) and heart rate (HR) during deep and shallow dives in the sea.